Comparing Recyclers and Non-Recyclers to Foster Pro-Environmental Behavior - Ioanna Ligoudi; Evangelia Karasmanaki; Georgios Tsantopoulos (Earth, 2025)
The voluntary basis on which recycling and energy saving are performed at households brings forward the need to better understand the profile of recyclers and non-recyclers and to make meaningful comparisons between them. Hence, the aim of this study is to compare recyclers’ and non-recyclers’ profiles and practices in order to detect areas that require policy and educational interventions. To achieve this aim, this study collected a representative sample of 384 citizens in a fast-growing urban center and compared recyclers and non-recyclers in terms of their environmental practices. The results showed that both groups identified environmental protection as their leading motive to recycle, while plastic and paper were the most recycled materials. An interesting difference between the two groups was that recyclers were more engaged in energy-saving, suggesting that recycling engagement may be associated with the adoption of energy-saving practices. The Internet was the leading information source across both groups, emphasizing the role it can play in spreading accurate and motivating messages about recycling and energy-saving. This study provides a useful and nuanced picture of recyclers’ and non-recyclers’ profiles and their differences, and as such, it can introduce new angles for the design of strategies for encouraging pro-environmental behavior.